Corrosion Reason Analysis of 13Cr110 Tubing in an Injection and Production Well of the Suqiao Gas Storage Group - Rui Cai; Jie Gui; Mingxing Li; Binbin Zhao; Xiaohong Bai; Guangxu Cheng (International Journal of Photoenergy)
Natural gas as a clean energy, its extensive use can alleviate energy crisis and environmental pollution and other problems. The storage and transportation of natural gas are of great significance to the standard use of natural gas. Suqiao gas storage reservoir is responsible for seasonal peak adjustment and emergency gas supply in the Beijing-Tianjin-Hebei region, and the corrosion of tubular goods is the most important issue. In this paper, the tubing composition analysis, metallographic structure analysis, mechanical property analysis, simulated corrosion test, corrosion morphology, and product analysis were carried out to analyze and study the corrosion behavior under the conditions, and suggestions were put forward to control the corrosion of the outer surface of the tubing.